Unusual presentation of anterior mediastinal teratoma with cavitary pulmonary lesion complicating Haemophilus influenzae - Babu, Sarath; Francis, Johny Vakayil; Jayan, Ponni; Louis, Varghese (International Journal of Contemporary Pediatrics, 2024)
Mediastinal teratomas are the most common extragonadal germ cell tumours. They account for approximately 15% of anterior mediastinal masses in adults and 25% in children. Teratomas are typically asymptomatic and are often discovered incidentally through imaging studies such as X-ray. However, some of them can present with a variety of symptoms due to mass effect, endocrine dysfunction, or complications resulting from rupture, which may lead to pleural effusion. We report a case of a mediastinal teratoma complicated by a cavitary pulmonary lesion in a 15-year-old female child. She presented with left-sided chest pain and intermittent cough. A chest X-ray (CXR) revealed a superior mediastinal mass lesion. Subsequent CT scan of the thorax demonstrated a lobulated cystic lesion, located in the anterior mediastinum. A CT-guided aspiration and biopsy of the mediastinal mass confirmed the diagnosis of a mature cystic teratoma. A bronchoalveolar lavage (BAL) showed evidence of Haemophilus influenzae. The child was managed with intravenous antibiotics targeting the pulmonary infection, followed by surgical excision of the teratoma.